The influences of dried Chicory root and White lupine added to food on jejunal morphology: experimental study - Makovicky, Peter; Volek, Zdenek; Uhlirova, Linda; Makovicky, Pavol (Gastroenterology and hepatology from bed to bench, 2018)
AIM: The objective of this work was to test the effects of adding dried Chicory root and White lupine food on small bowel morphology and compare it to a standard commercial diet. BACKGROUND: Various commercial gluten-free products, gluten-free raw materials and gluten-free plants are this time available on the food market, but there are still not enough information about their effect on the small bowel morphology. METHODS: Altogether thirty rabbits were used in this study. The control diet (C) contained common feed components. The first experimental diet (E1) contained (per kg) 60 g of dried chicory roots instead of barley, whereas the second experimental diet (E2) was based on white lupine seeds (cv. Amiga; 120 g per kg diet) instead of the soybean meal used in the control diet. The experiment started when the rabbits were 34-days old and lasted until they were 55-days old. At the end, one jejunal small bowel tissue was sampled, and both the heights and depths of the villi and crypts were measured. RESULTS: The highest villi were measured in the E1 (598.99 µm) group, mean in the C (590.30 µm) group and the lowest were in the E2 (563.74 µm) group. The most intense mucin villous positivity was observed in the E2 group, followed by the E1 group, and the weakest positivity was found in the visible C group. CONCLUSION: Chicory root has practical uses in gluten-free industries.
Keywords: Villi intestinalis; Gluten-free diet; Celiac disease; Small bowel; Nutrition